Portfolio Performance Measurement: Theory and Applications - Chen, Zhiwu; Knez, Peter J. (Review of Financial Studies, 1996)
Any admissible portfolio performance measure should satisfy four minimal conditions: it assigns zero performance to each reference portfolio and it is linear, continuous, and nontrivial. Such an admissible measure exists if and only if the securities market obeys the law of one price. A positive admissible measure exists if and only if there is no arbitrage. This article characterizes the (infinite) set of admissible performance measures. It is shown that performance evaluation is generally quite arbitrary. A mutual fund data set is also used to demonstrate how the measurement method developed here can be applied.